Pola Penggalangan Dana Pengalokasian Dana Dalam Lembaga Amil Zakat : Studi Kasus Pada Yayasan Al Azhar Peduli Umat dan Masyarakat Mandiri - Fitriyah, Fitriyah (Jurnal Ilmu Kesejahteraan Sosial, 2013)
This study was conducted to determine the pattern of fundraising as well as it’s allocation on Lembaga Amil Zakat (LAZ). This research was conducted with a qualitative research approach and descriptive research with research sites at 2 LAZ are Masyarakat Mandiri (MM) and Yayasan Al Azhar Peduli Umat (YAPU). The survey results revealed that the two institutions have a special division are tasked to conduct fundraising . Both MM and YAPU have internal and external sources of funds but YAPU also have a source of funds derived from the business. The type of funds obtained by the two institutions can be either cash or non material. Fundraising efforts from corporate, MM has requirements while YAPU not explicitly specify the requirements. The allocation of funds , MM and YAPU has different requirements